Katolicka pobożność i formy kultu w potrydenckiej Rzeczypospolitej. - Kaczor-Scheitler, Katarzyna (Poznańskie Studia Teologiczne, 2021)
Katarzyna Kaczor-Scheitler, PhD — assistant professor at the Department of Old Literature, Editing and Auxiliary Sciences at the University of Lodz. Author of books: Mistycyzm hiszpański w piśmiennictwie polskich karmelitanek XVII i XVIII wieku (Spanish Mysticism in the Literature of 17th and 18th-Century Polish Carmelites) (2005); Marianna Marchocka a św. Teresa z Avila (Marianna Marchocka and St. Theresa of Avila) (2009); Perswazja w wybranych medytacjach siedemnastowiecznych z klasztoru norbertanek na Zwierzyńcu (Persuasion in Selected 17th-Century Meditations from the Norbertine Monastery in Zwierzyniec) (2016). Co-editor of volumes of collected essays: Piśmiennictwo zakonne w dobie staropolskiej (Religious Writing in Old Poland) (2013) and Piotr Skarga — w czterechsetlecie śmierci (Piotr Skarga — on the 400th Anniversary of His Death) (2013). Author of works published in numerous conference proceedings and special volumes. Publishes her articles in Polish and foreign journals: “Acta Universitatis Lodziensis. Folia Litteraria Polonica”, “Analecta Praemonstratensia”, “Communio. Międzynarodowy Przegląd Teologiczny”, “Czytanie Literatury. Łódzkie Studia Literaturoznawcze”, “Pamiętnik Literacki”, “Poznańskie Studia Polonistyczne. Seria Literacka”, “Poznańskie Studia Teologiczne”, “Prace Polonistyczne”, “Przegląd Powszechny”, “Respectus Philologicus”, “Ruch Literacki”, “Studia Monastica”, “Świat i Słowo”, “Świat Tekstów. Rocznik Słupski”, “Tematy i Konteksty”. Main areas of interest: old religious literature, especially occasional, ascetic-mystical and meditative literature.